ARCHITECTURES FOR EXTREME-SCALE COMPUTING. - Torrellas, Josep (Computer (00189162), 2009)
The article focuses on the architectural challenges posed by the better performance of extreme scale-computers over high-end machines in 2009. It is stated that in increasing energy and power efficiency, an exa-op data center, a peta-op departmental server and a tera-op chip multiprocessor that consumes 20 megawatts (MW), 20 kilowatts (KW) and 20 watts (W) respectively might be needed. Low voltage and modest frequency circuits will reportedly be used to enable concurrency and locality.